Improving the management of an IT department by using a new developed computer application - Correia, Nuno Miguel de Sousa (2021)
This work has been developed outside of office hours, in combination with the work of IT Analyst and Project Manager in Philip Morris SA (Switzerland). The dissertation seeks solutions to real-life problems, specifically associated with the daily challenges faced by the managers and team members of the Information Technology department. It was acknowledged the need to enhance the management and assignment of tasks and projects to the team members, where the major issue resided on the understanding of the constraints affecting the work allocation and workload management. To solve the mentioned hurdles, it was needed to develop an appropriate tool, matching the specific needs while being economically efficient and easy to operate. The management was involved in various sharing sessions, allowing the work to be developed in line with the genuine pain-points and to be built accordingly to the needs and expectations of the end-users. The SWOT analysis and the Ishikawa diagram played an important role in the delimitation of the challenges and on documenting the improvement possibilities. Firstly, the problem assessment was done, then it was time to review the literature, searching for the core values and best practices in Project Management. Later, there was an extensive review of the Resources Allocation subject, by concept and objectives, and as a tool to efficiently merging the specificities of the resources and activities while considering an extensive group of constraints. Then, it was done a broad attempt to combine the concepts of the Manager as a human and a servant leader with a focus on team success, with the usage of Resources Allocation tools as indispensable instruments for the success of any Project. Later, the work arrives at its core, with the development of the Allocation Algorithm and the MS Excel® program that allows the Managers to properly register and assign the Projects and Tasks, considering the specificities and constraints in place. The developed tools have been validated and utilized by Managers while performing their daily management routines. The most relevant improvements indicated by the end-users have been, the centralization and availability of the information, the rapidity of new activities’ assignment, and the benefit of having a unified status tool that takes into consideration the team specificities. In the literature, there are different approaches related to the resources’ allocation and project management issues and challenges. However, many of the Researchers never left the concept development stage and several of them have only proposed theoretical approaches. In this work, more than build an algorithm and a program with a straightforward approach to the management challenges, it was prioritized the practicality of the model and the development of a purposeful tool – allowing the ideas to get off paper, implementing the tool and as result, effectively improving the management of activities and the human resources allocation.